A meta-analysis of social, economic, and institutional bottlenecks, barriers, and opportunities to more inclusive small and medium agribusiness in the ESA Region: a synthesis report - Enokenwa Baa, Ojongetakah; Nortje, Karen (International Water Management Institute (IWMI), 2023)
This report summarizes the meta-analysis findings on the social, economic, and institutional bottlenecks, barriers, and opportunities to more inclusive small and medium agribusiness in the ESA region. It serves as a link between the visible integration of GESI focus in WP1 and its interventions. The GESI framework1 brings about inclusive and scalable agribusiness innovations through targeted GESI support to UU ESA work packages 1-6. This framework will ensure that planned interventions under UU are designed and implemented to empower more women and youth as farmers, agribusiness owners, and actors with voice and visibility across agribusiness value chains (Nortje et al. 2023). The CGIAR Initiative on Diversification in East and Southern Africa (Ukama Ustawi- meaning “wellbeing”) is focused on diversification for resilient agribusiness ecosystems in Eastern and Southern Africa, also known as Ukama Ustawi (UU).